Understanding The Dynamic of International System Through The Lens of Complex System Approach - Indra Kusumawardhana (Universitas Airlangga, 2017)
The International Relations Study has undergone many changes in its dynamics,especially in view of the dynamic conditions of world politics. It directly influences the development of the IR study. This paper discusses how the theory of complex systems explain the dynamics of the international system after the end of the Cold War. Through the theory, the author seeks to see the changes that occur in interstate interaction, especially in the framework of thinking about the interests of each country. Interaction between countries then encourage the existence of different systems between one another, depending on how the country chooses interaction groups. The author also seeks the inter-state interaction that formed into an international system can be studied from the transition process to change the direction of interaction to see how the true international system is formed through the views of the theory of complex systems.